Association between Dioxin and Diabetes Mellitus in an Endemic Area of Exposure in Taiwan: A Population-Based Study. Issue 42 (October 2015) - Huang, Chien-Yuan; Wu, Cheng-Long; Yang, Yi-Ching; Chang, Jung-Wei; Kuo, Yau-Chang; Cheng, Ya-Yun; Wu, Jin-Shang; Lee, Ching-Chang; Guo, How-Ran
Abstract : Abstract: Dioxin has been recognized as an environmental endocrine disruptor, but epidemiology studies of its effects on type 2 diabetes mellitus (DM) found inconsistent results, especially in men. Therefore, we conducted a study in Taiwan to evaluate the association between exposure to dioxin and DM. We recruited participants in an area where the residents were exposed to dioxin released from a factory. Using 20 and 64 pg WHO98 -TEQDF /g lipid as the cut-offs, we categorized participants into 3 groups according to the level of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in the serum. We defined DM as a fasting plasma glucose level more than 126 mg/dl or an existing diagnosis. Of the 2898 participants, 425 patients of DM were identified, and we observed positive associations between dioxin and DM. After adjusting for age and body mass index (BMI), we found that a high serum dioxin level was an independent risk factor for DM (adjusted odds ratio [AOR] associated with 20–63 pg WHO98 -TEQDF /g lipid = 2.1, 95% confidence interval [95% CI] 1.5–2.9; AOR for ≥64 pg WHO98 -TEQDF /g lipid = 3.2, 95% CI 2.1–4.8). The findings are compatible with those in previous studies of PCDD/Fs. When we stratified the participants by sex, the serum dioxin level remained an independent risk factor for DM in both men and women. Exposure to dioxin is a risk factor for DM, independent of age and BMI in both men and women. Therefore, screening and intervention programs should be considered in endemic areas of exposure to dioxin.